Zirconium oxide ceramic powder, preparation method thereof and zirconium oxide sintered body

By controlling the specific surface area, particle size and grain characteristics of the zirconia ceramic powder, low-temperature sintering is achieved, solving the problem of high sintering temperature of dental zirconia, and obtaining a sintered body of high strength, high density and high light transmittance.

CN119707487AInactive Publication Date: 2025-03-28SHANDONG SINOCERA FUNCTIONAL MATERIAL CO LTD

Patent Information

Application Number
CN202411883228.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing dental zirconia has high sintering temperatures, high energy consumption, and permeability, strength and low-temperature aging performance cannot meet the growing demand.

Method used

By controlling the specific surface area, particle size, peak intensity ratio of 220 crystal plane/200 crystal plane and average crystal crystal diameter of the zirconia ceramic powder, a zirconia ceramic powder that can be sintered at low temperature and has a high sintering density at normal pressure was prepared.

Benefits of technology

Low-temperature sintering without adding sintering aid is achieved, and a zirconia sintered body with high strength, high sintering density and light transmittance is obtained, reducing energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707487A_ABST
    Figure CN119707487A_ABST
Patent Text Reader

Abstract

The invention discloses zirconia ceramic powder, a preparation method thereof and a zirconia sintered body, and relates to the technical field of zirconia. The zirconia ceramic powder comprises a solid solution formed by zirconia and a stabilizer, the specific surface area of the zirconia ceramic powder is 10-32 m < 2 > / g, the average particle size D50 is 0.1-0.3 [mu] m, the average particle size D90 is 0.2-0.5 [mu] m, and the peak intensity ratio of the crystal grain 220 crystal face / 200 crystal face of the zirconia ceramic powder obtained through powder X-ray diffraction measurement is 1.2-2.5. The zirconia ceramic powder in which the average crystallite diameter # imgabs0 # of the grains obtained from the (-111) plane peak of the grains of the zirconia ceramic powder in X-ray diffraction measurement satisfies the numerical range has a specific crystal plane orientation, so that low-temperature sintering can be realized without adding a sintering aid. And a sintered body having high strength and high sintering density can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of zirconium oxide, and in particular to a zirconium oxide ceramic powder and a preparation method thereof, and a zirconium oxide sintered body. Background Art

[0002] Zirconia is widely used in crushing, optics, decoration and dentistry. At present, the sintering temperature of dental zirconia is about 1500℃, which consumes a certain amount of energy. With the development of dental zirconia, higher requirements are put forward for beauty and performance. The existing high-temperature sintered zirconia cannot meet the growing needs in terms of permeability, strength and low-temperature aging performance.

[0003] Patent document 1 (CN113200567A) discloses a highly sintered active zirconium oxide powder, the particle size of which is 50-150 nm, and the sintered density at 1350-1450°C is 6.051-6.083 g / cm 3 The patent adopts the idea of ​​combining liquid phase precipitation method with hydrothermal method, and performs dry-wet gel conversion after liquid phase precipitation and before hydrothermal reaction, thereby preparing homogeneously dispersed tetragonal zirconium oxide powder. However, this method is more complicated than directly preparing zirconium oxide by hydrothermal method, and does not study the ceramic density below 1350℃.

[0004] Comparative Patent Document 2 (JP2023171832A) discloses a zirconium oxide powder comprising at least one of yttrium oxide, calcium oxide, magnesium oxide and cerium oxide as a stabilizer, wherein the proportion of monoclinic crystals in the zirconium oxide powder crystal phase is less than 0.5%, the average particle size is less than 0.5 μm, and the volume particle size is 100% of particles below 1 μm. This patent can achieve a sintering temperature of above 1200°C and below 1600°C in an air atmosphere by regulating the zirconium oxide crystal phase composition and particle size distribution, and the strength is between 350-600 MPa.

[0005] The ceramic sintering process is the accumulation of point contact of particles into surface contact. At the same time, the pores between the particles are eliminated, and a densely sintered ceramic is formed. Therefore, the sintering activity of ceramics is affected by the size of the particles and the pores between the particles. The particle size tested in Comparative Document 1 is the particle size of secondary particles. However, secondary particles are aggregates of primary particles. The agglomeration behavior of primary particles and the presence of sintering necks will affect the test of secondary particles. Comparative Document 2 regulates the size and distribution of gaps between primary particles to study the sintering activity. In summary, the improvement of sintering activity not only depends on the particle size and distribution of secondary particles and the uniformity of agglomeration of primary particles constituting secondary particles, the degree of agglomeration of coarse or dense stacking, but also requires the regulation of the primary particle size of the particles to obtain high sintering activity zirconia powder. Comparative Documents 1 and 2 only point out that the powder has high sintering activity, but do not directly study the sintering activity.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The object of the present invention is to provide a zirconia ceramic powder, a preparation method thereof and a zirconia sintered body. The present invention controls the specific surface area, particle size, peak intensity ratio of 220 crystal planes / 200 crystal planes and average crystallite diameter of the zirconia ceramic powder to obtain a zirconia ceramic powder that can be sintered at low temperature under normal pressure and has a high sintering density ceramic. Since the zirconia ceramic powder is a nanoparticle, the scattering cross section is small, the scattering on the grain boundary is reduced, the tetragonality is smaller, and the birefringence is also smaller, so the light transmittance of the obtained zirconia ceramic is improved, and high strength is also achieved.

[0008] The present invention is achieved in that:

[0009] In a first aspect, the present invention provides a zirconia ceramic powder, which comprises a solid solution formed by zirconium oxide and a stabilizer, wherein the specific surface area of ​​the zirconia ceramic powder is 10 to 32 m 2 / g, an average particle size D50 of 0.1 to 0.3 μm, an average particle size D90 of 0.2 to 0.5 μm, a peak intensity ratio of 220 crystal plane / 200 crystal plane of the zirconia ceramic powder measured by powder X-ray diffraction of 1.2 to 2.5, and an average crystallite diameter of the zirconia ceramic powder obtained by the (-111) plane peak of the zirconia ceramic powder grains in the X-ray diffraction measurement of

[0010] In an optional embodiment, the 2θ angle corresponding to the 220 crystal plane is 49.5° to 50.5°, the 2θ angle corresponding to the 200 crystal plane is 29.5° to 30.5°, and the 2θ angle corresponding to the (-111) crystal plane is 31° to 32°.

[0011] In an optional embodiment, the sintering starting point of the zirconia ceramic powder is lower than 1300° C., and the sintering starting point is obtained based on a DIL test.

[0012] In an optional embodiment, the stabilizer includes at least one of a Y source, a Ca source, a Mg source, and an Er source;

[0013] Preferably, the Y source includes one or more of yttrium oxide, yttrium nitrate, yttrium chloride and yttrium sulfate; preferably, the content of the Y source relative to the zirconia ceramic powder is 1.5-5 mol%;

[0014] Preferably, the Ca source includes one or more of calcium oxide, calcium carbonate and calcium chloride; preferably, the content of the Ca source relative to the zirconia ceramic powder is 4-8 mol%.

[0015] Preferably, the Mg source includes one or more of magnesium oxide, magnesium chloride and magnesium sulfate; preferably, the content of the Mg source relative to the zirconia ceramic powder is 6 to 13 mol%;

[0016] Preferably, the Er source is erbium oxide; preferably, the content of the Er source relative to the entire zirconium oxide powder is 3-5 mol%.

[0017] In an optional embodiment, the zirconia ceramic powder further includes at least one of 0.005-1wt% of a first dopant for producing a coloring effect and 0.005-1wt% of a second dopant for improving toughness and low temperature aging properties;

[0018] Preferably, the first dopant includes at least one of Fe, Er, Mn, Co, Cr, Tb, Pr, Nd, Eu and Ti;

[0019] Preferably, the second dopant is Al;

[0020] Preferably, the Al includes one or more of aluminum oxide, aluminum chloride and aluminum nitrate.

[0021] In a second aspect, the present invention provides a method for preparing a zirconia ceramic powder as described in any one of the aforementioned embodiments, comprising:

[0022] S1. Prepare a soluble zirconium salt into a solution with a zirconium ion concentration of 0.3-0.7 mol / L, perform a hydrothermal reaction at a pressure of 0.2-0.35 MPa and a temperature of 120-140° C. for 12-50 hours, add a stabilizer to the product, and obtain a reaction solution;

[0023] S2, drying the reaction solution and calcining it, the calcination temperature is 950-1150° C., the heating rate is 2.5-6° C. / min, and the insulation time is 1-5h to obtain a calcined powder;

[0024] S3. Ball-milling the calcined powder to obtain zirconium oxide ceramic powder, with the ball-milling time being 0.5-6 h.

[0025] In an optional embodiment, the zirconium salt includes at least one of zirconium oxychloride, zirconium acetate and zirconium carbonate.

[0026] In a third aspect, the present invention provides a zirconia sintered body, which comprises zirconia ceramic powder prepared by the zirconia ceramic powder as described in the aforementioned embodiment or the method for preparing zirconia ceramic powder as described in any of the aforementioned embodiments, and sintered by normal pressing.

[0027] In an optional embodiment, the pressureless sintering includes sequentially performing dry pressing, isostatic pressing, pre-sintering and sintering;

[0028] Preferably, the dry pressing pressure of the dry pressing molding is 120-300 MPa, and the dry pressing time is 30-180 s;

[0029] Preferably, the isostatic pressing pressure of the isostatic pressing is 150-350 MPa, and the isostatic pressing time is 5-20 min;

[0030] Preferably, the pre-sintering temperature is 800-1100° C., and the pre-sintering time is 15h-60h;

[0031] Preferably, the sintering temperature is 1150° C.-1400° C., and the sintering time is 30 min-10 h.

[0032] In an optional embodiment, the zirconia sintered body has a sintering density of ≥99%, a strength of 700-1300 MPa, and a permeability of 38-44%.

[0033] The present invention has the following beneficial effects:

[0034] The present invention provides a zirconium oxide ceramic powder having a specific surface area of ​​10 to 32 m 2 / g, the average particle size D50 is 0.1-0.3μm, the average particle size D90 is 0.2-0.5μm, the peak intensity ratio of the 220 crystal plane / 200 crystal plane of the zirconia ceramic powder measured by powder X-ray diffraction is 1.2-2.5, and the average crystallite diameter of the zirconia ceramic powder obtained by the (-111) plane peak of the zirconia ceramic powder grains in the X-ray diffraction measurement is The particle size D50 of zirconia ceramic powder will affect the specific surface area and sintering activity of the powder, thereby affecting the solid-phase diffusion rate and the interaction between sintered particles during the sintering process. Zirconia ceramic powder with a smaller particle size has a larger specific surface area, which can increase the mutual contact area between powder particles, improve the solid-phase diffusion rate, increase the sintering activity, and make the sintering temperature relatively low. At the same time, the particle size D90 needs to be controlled. If D90 is too large, it means that there are many large particles, causing molding defects and affecting the sintering performance, strength and permeability. The peak intensity ratio of 220 crystal plane / 200 crystal plane is controlled in the range of 1.2-2.5, which can ensure that the molding is not easy to disintegrate and the sintered body has excellent strength. The average crystallite diameter of the grains is The pore defects of the grains can be ensured to be small, which effectively avoids affecting the strength and permeability of the sintered body, realizes low-temperature sintering at 1150-1400°C, and reduces energy consumption. In the present invention, the specific surface area, particle size, peak intensity ratio of 220 crystal planes / 200 crystal planes and average crystallite diameter of the zirconia ceramic powder are controlled. The zirconia ceramic powder that meets the above numerical range has a specific crystal plane orientation, so low-temperature sintering can be achieved without adding a sintering aid, and a sintered body with high strength and high sintering density can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0036] Figure 1 A DIL curve diagram of the zirconia ceramic powder provided in Example 1 of the present invention;

[0037] Figure 2 A DIL curve diagram of the zirconia ceramic powder provided in Example 3 of the present invention;

[0038] Figure 3 A DIL curve diagram of the zirconia ceramic powder provided in Example 8 of the present invention;

[0039] Figure 4 A DIL curve diagram of the zirconia ceramic powder provided in Example 12 of the present invention;

[0040] Figure 5 A DIL curve diagram of the zirconia ceramic powder provided in Comparative Example 1 of the present invention;

[0041] Figure 6 This is a DIL curve diagram of the zirconia ceramic powder provided in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0043] The present invention provides a zirconium oxide ceramic powder, which comprises a solid solution formed by zirconium oxide and a stabilizer. The specific surface area of ​​the zirconium oxide ceramic powder is 10 to 32 m 2 / g, the average particle size D50 is 0.1-0.3μm, the average particle size D90 is 0.2-0.5μm, the peak intensity ratio of the 220 crystal plane / 200 crystal plane of the zirconia ceramic powder measured by powder X-ray diffraction is 1.2-2.5, and the average crystallite diameter of the zirconia ceramic powder obtained by the (-111) plane peak of the zirconia ceramic powder grains in the X-ray diffraction measurement is

[0044] In the present invention, the specific surface area, particle size, peak intensity ratio of 220 crystal planes / 200 crystal planes and average crystallite diameter of the zirconia ceramic powder are controlled. The zirconia ceramic powder satisfying the above numerical range has a specific crystal plane orientation, so low-temperature sintering can be achieved without adding sintering aids, and a sintered body with high strength and high sintering density can be obtained.

[0045] Specifically, the particle size D50 of zirconia ceramic powder will affect the specific surface area and sintering activity of the powder, thereby affecting the solid phase diffusion rate and the interaction between sintering particles during the sintering process. Zirconia ceramic powder with a smaller particle size has a larger specific surface area, which can increase the mutual contact area between powder particles, improve the solid phase diffusion rate, increase the sintering activity, and make the sintering temperature relatively low. At the same time, the particle size D90 needs to be controlled. If D90 is too large, it means that there are many large particles, causing molding defects and affecting the sintering performance, strength and permeability. When the particle size is too small and the specific surface is too large: particles with too small particle size are dispersed after calcination. Due to the high surface energy, it is easy to agglomerate, the dispersion effect is not good, and the corresponding powder has poor formability when preparing sintered bodies, deteriorating strength, permeability and toughness. When the particle size is too large and the specific surface is too small: the corresponding powder with too large particle size has a small specific surface area, low surface energy, slow solid phase migration rate, and is not easy to sinter at low temperatures, and the corresponding permeability and strength are also deteriorated.

[0046] The peak intensity ratio of the 220 crystal plane / 200 crystal plane ((220) / (200)) of the zirconium oxide ceramic powder grains is 1.2-2.5. When it is greater than the upper limit, the particles are prone to disintegration during molding. When it is less than the lower limit, the strength of the sintered body tends to decrease. Among them, the 2θ angle corresponding to the 220 crystal plane is 49.5° to 50.5°, and the 2θ angle corresponding to the 200 crystal plane is 29.5° to 30.5°.

[0047] The average crystallite diameter of the primary particles of the zirconium oxide ceramic powder obtained by measuring the (-111) peak of the zirconium oxide ceramic powder grains by powder X-ray diffraction is When the above average crystallite diameter is too large, the zirconium oxide grains grow excessively, resulting in an increase in the gaps within the particles. On the one hand, the formability is affected, resulting in an increase in pore defects, affecting the strength and permeability of the sintered body. On the other hand, the contact between the grains is reduced, and the energy transfer during the sintering process is weakened, making it difficult to achieve low-temperature sintering. When the above average crystallite diameter is too small, the grain boundaries within the particles increase, and the incident light passes through the grain boundaries, which will inevitably cause continuous reflection and refraction of the light, resulting in a decrease in transmittance. Among them, the 2θ angle corresponding to the (-111) crystal plane is 31°~32°.

[0048] Furthermore, the sintering starting point of the zirconia ceramic powder is lower than 1300°C, and the sintering starting point is obtained based on the DIL test. By screening the sintering activity, it can be ensured that a zirconia sintered body with high strength and high sintering density can be obtained under low temperature conditions of 1150°C-1400°C.

[0049] The stabilizer includes at least one of a Y source, a Ca source, a Mg source, and an Er source.

[0050] In some embodiments, the Y source includes but is not limited to one or more of yttrium oxide, yttrium nitrate, yttrium chloride and yttrium sulfate; preferably, the content of the Y source relative to the zirconia ceramic powder is 1.5-5 mol%; for example, it can be any one of 1.5 mol%, 2 mol%, 2.5 mol%, 3 mol%, 3.5 mol%, 4 mol%, 4.5 mol%, 5 mol% or a range between any two of them.

[0051] In some embodiments, the Ca source includes but is not limited to one or more of calcium oxide, calcium carbonate and calcium chloride; preferably, the content of the Ca source relative to the zirconia ceramic powder is 4-8 mol%. For example, it can be any one of 4 mol%, 5 mol%, 5.5 mol%, 6 mol%, 6.5 mol%, 7 mol%, 7.5 mol%, 8 mol%, or a range between any two of them.

[0052] In some embodiments, the Mg source includes but is not limited to one or more of magnesium oxide, magnesium chloride and magnesium sulfate; preferably, the content of the Mg source relative to the zirconia ceramic powder is 6 to 13 mol%; for example, it can be any one of 6 mol%, 7 mol%, 8 mol%, 9 mol%, 10 mol%, 11 mol%, 12 mol%, 13 mol% or a range value between any two of them.

[0053] In some embodiments, the Er source includes but is not limited to erbium oxide; preferably, the content of the Er source relative to the total zirconium oxide powder is 3-5 mol%, for example, 3 mol%, 3.5 mol%, 4 mol%, 4.5 mol%, 5 mol%, or any range between two of them.

[0054] Furthermore, the zirconium oxide ceramic powder further includes at least one of 0.005-1wt% of a first dopant for producing a coloring effect and 0.005-1wt% of a second dopant for improving toughness and low temperature aging properties;

[0055] Preferably, the first dopant includes at least one of Fe, Er, Mn, Co, Cr, Tb, Pr, Nd, Eu and Ti; the second dopant is Al; Al includes but is not limited to one or more of aluminum oxide, aluminum chloride and aluminum nitrate.

[0056] The first dopant and the second dopant mentioned above can be added to the zirconia ceramic powder at any stage of the preparation process. The first dopant and the second dopant can be partially loaded on the surface of zirconia and partially only form a composition with zirconia; or they can all be in a free state and only form a composition with zirconia.

[0057] The present invention provides a method for preparing zirconium oxide ceramic powder, which comprises the following steps:

[0058] S1. A soluble zirconium salt is prepared into a solution with a zirconium ion concentration of 0.3-0.7 mol / L, and a hydrothermal reaction is carried out at a pressure of 0.2-0.35 MPa and a temperature of 120-140° C. for 12-50 hours, and a stabilizer is added to the product to obtain a reaction solution; the zirconium salt includes at least one of zirconium oxychloride, zirconium acetate and zirconium carbonate.

[0059] S2. The reaction solution is dried and then calcined at a temperature of 950-1150° C., a heating rate of 2.5-6° C. / min, and a heat preservation time of 1-5 h to obtain a calcined powder.

[0060] S3. Ball milling the calcined powder to obtain zirconium oxide ceramic powder, the ball milling time is 0.5-6h.

[0061] In the present invention, by controlling the concentration of the zirconium salt solution and the conditions of the hydrothermal reaction, better zirconium oxide particle size, specific surface area and crystallinity can be obtained. By adding a stabilizer to the product, a solid solution is formed with zirconium oxide during the subsequent drying and calcining process, and zirconium oxide ceramic powder can be obtained by grinding.

[0062] In the present invention, the concentration of the zirconium salt solution and the conditions of the hydrothermal reaction need to be strictly controlled. If the concentration of the zirconium salt solution is too high, the reaction system will have more nuclei, and the grains will be too fine and prone to agglomeration; if the concentration of the solution is too low, there will be less nucleation, and the grains will easily grow, resulting in reduced activity; if the hydrothermal temperature is too low, the pressure is too low, and the reaction time is too short, it will lead to incomplete grain development, excessive hydrates, and serious adhesion and agglomeration; if the hydrothermal temperature is too high, the pressure is too high, and the reaction time is too long, the grains will continue to grow and the activity of the powder will be reduced.

[0063] In addition, the present invention provides a zirconia sintered body, which is formed by sintering the above zirconia ceramic powder under normal pressure.

[0064] Atmospheric pressure sintering includes dry pressing, isostatic pressing, pre-sintering and sintering in sequence; specifically, the atmospheric pressure sintering includes dry pressing for 30-180s at a dry pressing pressure of 120-300MPa, isostatic pressing for 5-20min at an isostatic pressing pressure of 150-350MPa, pre-sintering at a pre-sintering temperature of 800-1100°C for 15-60h, and then sintering at 1150°C-1400°C for 30min-10h to obtain a zirconia sintered body with high sintering density. The sintering density of the zirconia sintered body is ≥99%, the strength is 700-1300MPa, and the permeability is 38-44%.

[0065] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0066] The present invention provides zirconia ceramic powder, zirconia pre-calcined body and zirconia sintered body as shown in Table 1 and Table 2, and tests are performed on them.

[0067] Detection methods include:

[0068] (1) Specific surface area measurement: The specific surface area was measured by the BET method using a specific surface area analyzer.

[0069] (2) Particle size determination: The particle size distribution was determined using a laser particle size tester.

[0070] (3) Peak intensity and crystal size determination: The crystal structure of solid powder was determined using an X-ray diffractometer.

[0071] (4) Sintering activity determination: The DIL method was used to test the sintering activity using a high temperature thermal expansion instrument. The results are shown in Table 1 and Figure 1-Figure 6 Shown in.

[0072] (5) Preparation and determination of zirconia sintered bodies: The zirconia sintered bodies of the examples and comparative examples were sintered according to a heating program, wherein the temperature was increased to 1200° C. at 10° C. / min and kept at that temperature for 2 h, and then increased to the sintering temperature at 5° C. / min and kept at that temperature for 2 h.

[0073] The relative sintered density of the zirconia sintered body is calculated as follows:

[0074] Relative sintering density (%) = (actual sintering density / theoretical sintering density) × 100;

[0075] The theoretical sintered density (denoted as ρ0) is a value calculated by the following formula (1):

[0076] ρ0=100 / [(Y / 3.987)+(100-Y) / ρz] (1);

[0077] Here, Y is the aluminum oxide concentration (weight %), and ρz is a value calculated by the following formula (2):

[0078] ρz=[124.25(100-X)+[molecular weight of stabilizer]×X] / [150.5(100+X)A 2 C] (2);

[0079] In formula (2), the molecular weight of the stabilizer is 225.81 when the stabilizer is Y2O3, and 382.52 when the stabilizer is Er2O3. X is the concentration of the stabilizer (mol %).

[0080] In addition, A and C are values ​​calculated by the following equations (3) and (4), respectively.

[0081] A=0.5080+0.06980X / (100+X) (3);

[0082] C=0.5195-0.06180X / (100+X) (4);

[0083] In formula (1), the theoretical sintered density varies depending on the composition of the powder. For example, when the yttrium oxide content is 3 mol%, it is 6.098 g / cm 3 , when the yttrium oxide content is 5.5 mol%, it is 6.051 g / cm 3 (When Al2O3=0 weight %).

[0084] When the stabilizer is CaO, ρz is a value calculated by the following formula (5).

[0085] ρz=-0.0400(molar concentration of CaO)+6.1700 (5).

[0086] In addition, the theoretical sintered density (denoted as ρ1) when the colorant is included is calculated as follows:

[0087] ρ1=100 / [(Z / V)+(100-Z) / ρ0] (6);

[0088] Where Z is the colorant concentration (weight %), V is the colorant theoretical density (g / cm 3 ); Regarding the theoretical density of the colorant, Fe2O3 is 5.24g / cm 3 , Er2O3 is 8.64g / cm 3 , MnO2 is 5.03g / cm 3 , CoO is 6.10 g / cm 3, Cr2O3 is 5.22g / cm 3 , Tb4O7 is 7.80g / cm 3 , Pr2O3 is 7.13g / cm 3 , Nd2O3 is 7.24g / cm 3 , Eu2O3 is 7.42g / cm 3 , TiO2 is 4.23g / cm 3 .

[0089] The actual sintered density of the zirconia sintered body was tested by the Archimedean drainage method.

[0090] The strength was tested by the three-point bending strength method using a universal testing machine. The light transmittance was tested by the spectrophotometer method using a benchtop visible spectrophotometer.

[0091] Please refer to Table 1 and Table 2 for the test results.

[0092] Table 1. Indexes of zirconia ceramic powder

[0093]

[0094] 11

[0096]

[0097] Table 2. Performance parameters of zirconia calcined and sintered bodies

[0098]

[0099]

[0100] Regarding the light transmittance of Examples 10, 11 and 13: After the colorant is added, a solid solution is formed, resulting in changes in the grain boundary structure, and irregular reflection, refraction and scattering of the incident light when passing through the grain boundary, thereby reducing the light transmittance. Compared with Example 10, Comparative Example 9 only changes the ball milling time, and the performance is significantly deteriorated, and the light transmittance is significantly reduced.

[0101] It can be seen from Tables 1 and 2 above that when the specific surface area, particle size, crystal plane peak intensity and grain size of the zirconia ceramic powder are within the scope of the present invention, its initial sintering temperature is significantly lower than that of Comparative Examples 1-4, and the sintering density, strength and light transmittance of the zirconia sintered body are also significantly better than those of Comparative Examples 1-4.

[0102] The particle size D50 of ceramic powder will affect the specific surface area and sintering activity of the powder, thereby affecting the solid phase diffusion rate and the interaction between sintering particles during the sintering process. Specifically, ceramic powder with a smaller particle size has a larger specific surface area, which can increase the mutual contact area between powder particles, improve the solid phase diffusion rate, increase the sintering activity, and make the sintering temperature relatively low. At the same time, the particle size D90 needs to be controlled. If D90 is too large, it means that there are many large particles, causing molding defects and affecting the sintering performance, strength and permeability.

[0103] The particle size is too small and the specific surface area is too large: Particles with a particle size that is too small are dispersed after calcination. Due to the high surface energy, they are prone to agglomeration, resulting in poor dispersion effect. In addition, the corresponding powder has poor formability when preparing sintered bodies, and deteriorates strength, permeability and toughness.

[0104] The particle size is too large and the specific surface area is too small: The corresponding powder with a particle size that is too large has a small specific surface area, low surface energy, slow solid phase migration rate, and is not easy to sinter at low temperatures, and the corresponding permeability and strength also deteriorate.

[0105] The average crystallite diameter of the primary particles of zirconium oxide obtained by measuring the (-111) peak of zirconium oxide crystal grains by powder X-ray diffraction is When the above average crystallite diameter is too large, the zirconium oxide grains grow excessively, resulting in an increase in the gaps within the particles. On the one hand, the formability is affected, resulting in an increase in pore defects, affecting the strength and permeability of the sintered body. On the other hand, the contact between the grains is reduced, and the energy transfer during the sintering process is weakened, making it difficult to achieve low-temperature sintering. When the above average crystallite diameter is too small, the grain boundaries within the particles increase, and the incident light passes through the grain boundaries, which will inevitably cause continuous reflection and refraction of the light, resulting in a decrease in light transmittance.

[0106] The peak intensity ratio of the 220 crystal plane / 200 crystal plane of the zirconium oxide grains ((220) / (200)) is 1.2-2.5. When it is greater than the above upper limit, the particles are prone to disintegration during molding. When it is less than the above lower limit, the strength of the sintered body tends to decrease.

[0107] In addition, the present invention also provides corresponding preparation methods of the above product embodiments and product comparison examples.

[0108] Method Example 1

[0109] 58.57 g of zirconium carbonate was dissolved in 1 L of pure water to prepare a solution with a zirconium ion concentration of 0.3 mol / L. The solution was subjected to hydrothermal reaction at a pressure of 0.24 MPa and a temperature of 120°C for 16 h. 1.11 g (3 mol%) of yttrium oxide was added to the product as a stabilizer. The resulting reaction solution was dried and calcined at a calcination temperature of 1000°C, a heating rate of 3°C / min, and a holding time of 4 h. The solution was then ball milled for 0.5 h to obtain zirconium oxide ceramic powder.

[0110] The zirconia ceramic powder was dry pressed for 120 seconds at a dry pressing pressure of 120 MPa, isostatically pressed for 12 minutes at an isostatic pressing pressure of 180 MPa, and pre-sintered at a pre-sintering temperature of 1000°C for 40 hours to obtain the zirconia calcined body of Example 1. The zirconia calcined body was densified by sintering at 1250°C for 5 hours, and the relative sintered density was 99.6%.

[0111] Method Example 2

[0112] This embodiment is basically the same as method embodiment 1, except that 58.57g of zirconium carbonate is replaced by 136.66g of zirconium carbonate, that is, the zirconium ion concentration is replaced by 0.7mol / L. The zirconia ceramic powder and zirconia pre-calcined body of embodiment 2 are obtained in the same manner as embodiment 1. The zirconia pre-calcined body is densely sintered at 1250°C, and the relative sintered density is 99.5%.

[0113] Method Example 3

[0114] This embodiment is basically the same as method embodiment 1, except that 58.57g of zirconium carbonate is replaced by 66.35g of zirconium oxychloride and the pressure is changed to 0.35MPa, and the zirconia ceramic powder of embodiment 3 is obtained in the same manner as embodiment 1; except that the pre-firing temperature is replaced with 1100°C to obtain the zirconia pre-firing body of embodiment 3, the zirconia pre-firing body is sintered to density at 1350°C, and the relative sintering density is 99.8%.

[0115] Method Example 4

[0116] This embodiment is basically the same as method embodiment 1, except that the hydrothermal reaction temperature is replaced by 140°C and the hydrothermal time is replaced by 50 hours. The zirconia ceramic powder and zirconia pre-calcined body of embodiment 4 are obtained in the same manner as embodiment 1. The zirconia pre-calcined body is densely sintered at 1350°C, and the relative sintered density is 99.7%.

[0117] Method Example 5

[0118] This embodiment is basically the same as method embodiment 1, except that the stabilizer is replaced by 1.85g (5mol%) yttrium oxide and the calcination temperature is replaced by 1050°C, the zirconia ceramic powder of embodiment 5 is obtained in the same manner as embodiment 1; except that the pre-firing temperature is replaced by 900°C, the zirconia pre-firing body of embodiment 5 is obtained, and the zirconia pre-firing body is densely sintered at 1150°C, with a relative sintering density of 99.6%.

[0119] Method Example 6

[0120] This embodiment is basically the same as method embodiment 1, except that the hydrothermal time is replaced with 130°C and the stabilizer is replaced with 0.93g (1.5mol%) yttrium oxide. The zirconia ceramic powder and zirconia pre-calcined body of embodiment 6 are obtained in the same manner as embodiment 1. The zirconia pre-calcined body is densely sintered at 1400°C, and the relative sintered density is 99.5%.

[0121] Method Example 7

[0122] This embodiment is basically the same as method embodiment 1, except that the stabilizer is replaced by 3.67g (5mol%) calcium chloride, the calcination temperature is replaced by 1100°C, and the ball milling time is replaced by 5h. The zirconia ceramic powder and zirconia pre-calcined body of embodiment 7 are obtained in the same manner as embodiment 1. The zirconia pre-calcined body is densely sintered at 1350°C, and the relative sintering density is 99.7%.

[0123] Method Example 8

[0124] This embodiment is basically the same as method embodiment 1, except that the calcination temperature is replaced by 1050°C, the heating rate is replaced by 6°C / min, and the holding time is replaced by 1h. The zirconia ceramic powder and zirconia pre-calcined body of embodiment 8 are obtained in the same manner as embodiment 1. The zirconia pre-calcined body is densely sintered at 1400°C, and the relative sintered density is 99.6%.

[0125] Method Example 9

[0126] This embodiment is basically the same as method embodiment 1, except that the calcination temperature is replaced with 1150°C and the ball milling time is replaced with 6 hours. The zirconia ceramic powder of embodiment 9 is obtained in the same manner as embodiment 1, except that the pre-firing temperature is replaced with 1050°C to obtain the zirconia pre-firing body of embodiment 9. The zirconia pre-firing body is densely sintered at 1350°C, and the relative sintering density is 99.7%.

[0127] Method Example 10

[0128] This embodiment is basically the same as method embodiment 1, except that the stabilizer is replaced by 1.48g (4mol%) yttrium oxide, the calcination temperature is replaced by 950°C and 0.2wt% iron oxide is added. The zirconia ceramic powder of embodiment 10 is obtained in the same manner as embodiment 1, except that the pre-firing temperature is replaced by 850°C to obtain the zirconia pre-fired body of embodiment 10. The zirconia pre-fired body is densely sintered at 1150°C, and the relative sintering density is 99.7%.

[0129] Method Example 11

[0130] This embodiment is basically the same as method embodiment 1, except that the hydrothermal pressure is changed to 0.3MPa, the hydrothermal temperature is changed to 130°C and the stabilizer is replaced with 4mol% of bait oxide. The zirconia ceramic powder of embodiment 11 is obtained in the same manner as embodiment 1, except that the pre-firing temperature is replaced with 950°C to obtain the zirconia pre-firing body of embodiment 11. The zirconia pre-firing body is densely sintered at 1350°C, and the relative sintering density is 99.5%.

[0131] Method Example 12

[0132] This embodiment is basically the same as method embodiment 1, except that 58.57g of zirconium carbonate is replaced by 154.83g of zirconium oxychloride and 0.1wt% of alumina is added. The zirconium oxide ceramic powder and zirconium oxide pre-calcined body of embodiment 12 are obtained in the same manner as embodiment 1. The zirconium oxide pre-calcined body is densely sintered at 1150°C, and the relative sintered density is 99.7%.

[0133] Method Example 13

[0134] This embodiment is basically the same as method embodiment 1, except that 0.02wt% of aluminum oxide and 0.005wt% of manganese oxide are added, the zirconium oxide ceramic powder of embodiment 13 is obtained in the same manner as embodiment 1, except that the dry pressing pressure is replaced by 150MPa and the isostatic pressing pressure is replaced by 240MPa, the zirconium oxide calcined body of embodiment 13 is obtained, and the zirconium oxide calcined body is densely sintered at 1350°C, and the relative sintering density is 99.5%.

[0135] Method Example 14

[0136] Zirconia powder was prepared by chemical precipitation method: 66.35g zirconium oxychloride was dissolved in 1L pure water to prepare a solution with a zirconium ion concentration of 0.3mol / L, 2.70g (3mol%) yttrium nitrate was added as a stabilizer, 0.5wt% anhydrous ethanol was added as a dispersant, NH3·H2O was added dropwise at a rate of 80mL / min until the pH was adjusted to 9 and slurry was beaten for 1h, the chloride ions were washed with deionized water, then dried and calcined at a calcination temperature of 900°C, a heating rate of 3°C / min, and a holding time of 4h, followed by ball milling for 0.5h to obtain zirconium oxide ceramic powder.

[0137] The zirconia calcined body of Example 14 was obtained by treating in the same manner as in Example 1. The zirconia calcined body was densely sintered at 1350° C., and the relative sintered density was 99.2%.

[0138] Method Example 15

[0139] Zirconium oxide powder was prepared by alcohol salt hydrolysis method: 54.8g zirconium isopropoxide was dissolved in 1L pure water to prepare a solution with a zirconium ion concentration of 0.3mol / L, 2.70g (3mol%) yttrium nitrate was added as a stabilizer, 300ml ammonia solution was added to 500ml isopropanol to obtain a hydrolyzing agent, the hydrolyzing agent was directly mixed with the zirconium isopropoxide solution and stirred for 30min to obtain a precursor gel, the obtained product was dried and calcined at a calcination temperature of 1000°C, a heating rate of 3°C / min, and a holding time of 4h, followed by ball milling for 0.5h to obtain zirconium oxide ceramic powder.

[0140] The zirconium oxide calcined body of Example 14 was obtained by treating in the same manner as in Example 1. The zirconium oxide calcined body was dense after sintering at 1400° C., and the relative sintered density was 99.4%.

[0141] Method Comparative Example 1

[0142] This comparative example is basically the same as method example 1, except that 178.13 g of zirconium oxychloride is dissolved in 1 L of pure water to prepare a solution with a zirconium ion concentration of 1.0 mol / L and the calcination temperature is lowered to 900°C. The zirconium oxide ceramic powder and zirconium oxide pre-calcined body of comparative example 1 are obtained in the same manner as in example 1. The zirconium oxide pre-calcined body is not dense when sintered at 1400°C, and the relative sintered density is 98.7%.

[0143] Method Comparative Example 2

[0144] This comparative example is basically the same as method example 1, except that the pressure is replaced by 0.1 MPa, the reaction temperature is replaced by 150°C and the reaction time is replaced by 30 h. The zirconia ceramic powder and zirconia pre-calcined body of comparative example 2 are obtained in the same manner as example 1. The zirconia pre-calcined body is not dense when sintered at 1400°C, and the relative sintered density is 97.3%.

[0145] Method Comparative Example 3

[0146] This comparative example is basically the same as method example 1, except that the calcination temperature is replaced with 1200°C. The zirconia ceramic powder of comparative example 3 is obtained in the same manner as example 1. The zirconia ceramic powder cannot be dry pressed, so the zirconia pre-calcined body is not obtained.

[0147] Method Comparative Example 4

[0148] This comparative example is basically the same as method example 1, except that the dry pressing pressure is replaced by 80 MPa and the pre-sintering temperature is replaced by 700°C. The zirconia ceramic powder and zirconia pre-sintered body of comparative example 4 are obtained in the same manner as example 1. The zirconia pre-sintered body is not dense when sintered at 1400°C, and the relative sintering density is 95.9%.

[0149] Method Comparative Example 5

[0150] This comparative example is basically the same as method example 1, except that the zirconium ion concentration in this comparative example is 1 mol / L. In the same manner as example 1, a zirconium oxide ceramic powder and a zirconium oxide calcined body of comparative example 5 were obtained, and the zirconium oxide calcined body was not dense when sintered at 1400° C., and the relative sintered density was 97.9%.

[0151] Method Comparative Example 6

[0152] This comparative example is basically the same as method example 1, except that the pressure of the hydrothermal reaction in this comparative example is 0.5 MPa. In the same manner as example 1, the zirconia ceramic powder and zirconia calcined body of comparative example 5 were obtained, and the zirconia calcined body was not dense when sintered at 1400° C., and the relative sintered density was 98.6%.

[0153] Method Comparative Example 7

[0154] This comparative example is basically the same as method example 1, except that the temperature of the hydrothermal reaction in this comparative example is 150° C. In the same manner as example 1, the zirconia ceramic powder and zirconia calcined body of comparative example 5 were obtained, and the zirconia calcined body was not dense when sintered at 1400° C., and the relative sintered density was 97.2%.

[0155] Method Comparative Example 8

[0156] This comparative example is basically the same as method example 1, except that the hydrothermal reaction time in this comparative example is 8 hours. The zirconium oxide ceramic powder and zirconium oxide calcined body of comparative example 8 are obtained in the same manner as example 1. The zirconium oxide calcined body is not densely sintered, and water is absorbed during the density test, so the density cannot be obtained.

[0157] Method Comparative Example 9

[0158] This comparative example is basically the same as Example 10, except that the ball milling dispersion is performed for 7 hours in this comparative example. The zirconium oxide ceramic powder and zirconium oxide calcined body of Comparative Example 9 are obtained in the same manner as Example 1. The zirconium oxide calcined body is not dense when sintered at 1400° C., and the relative sintering density is 98.5%.

[0159] Method Comparative Example 10

[0160] Taking Example 1 in CN202180007063.8 as a comparative example, the specific operation is as follows: 213 g of a 25 mass % sodium sulfate aqueous solution and 450 g of a 16 mass % zirconium oxychloride aqueous solution (acid concentration: 1N) converted to ZrO2 are heated to 95°C respectively (process 1).

[0161] Thereafter, in order to adjust the SO42- / ZrO2 mass ratio of the mixed solution to 0.50, the heated aqueous solutions were brought into contact with each other for 2 minutes (step 2).

[0162] Next, the obtained reaction liquid containing basic zirconium sulfate was maintained at 95° C. and aged for 4 hours to obtain basic zirconium sulfate (step 3).

[0163] Next, after the aged solution is cooled to room temperature, an aqueous solution of yttrium chloride at 10 mass % in terms of Y2O3 is added so that Y2O3 is 3 mol %, and the mixture is uniformly mixed (step 4).

[0164] Next, a 25% by mass sodium hydroxide aqueous solution was added to the obtained mixed solution to neutralize it to a pH of 13 or more, thereby generating a hydroxide precipitate (step 5).

[0165] The obtained hydroxide precipitate was filtered, washed thoroughly with water, and dried at 105° C. for 24 hours. The dried hydroxide was heat treated at 960° C. (calcination temperature) for 2 hours in air to obtain an unground zirconia powder (yttria-stabilized zirconia powder) (step 6).

[0166] To the obtained unground yttria-stabilized zirconia powder, 0.25 mass % of alumina powder with an average primary particle size of 0.1 μm was added relative to the yttria-stabilized zirconia powder, and the mixture was ground and mixed for 40 hours in a wet ball mill using water as a dispersion medium. Zirconia beads used in grinding. The zirconia slurry obtained after grinding was dried at 110° C. to obtain the zirconia powder of Comparative Example 10, which was sintered densely at 1200° C. with a relative sintered density of 99.1%.

[0167] In summary, the present invention provides a zirconium oxide ceramic powder having a specific surface area of ​​10 to 32 m 2 / g, the average particle size D50 is 0.1-0.3μm, the average particle size D90 is 0.2-0.5μm, the peak intensity ratio of the 220 crystal plane / 200 crystal plane of the zirconia ceramic powder measured by powder X-ray diffraction is 1.2-2.5, and the average crystallite diameter of the zirconia ceramic powder obtained by the (-111) plane peak of the zirconia ceramic powder grains in the X-ray diffraction measurement is The particle size D50 of zirconia ceramic powder will affect the specific surface area and sintering activity of the powder, thereby affecting the solid-phase diffusion rate and the interaction between sintered particles during the sintering process. Zirconia ceramic powder with a smaller particle size has a larger specific surface area, which can increase the mutual contact area between powder particles, improve the solid-phase diffusion rate, increase the sintering activity, and make the sintering temperature relatively low. At the same time, the particle size D90 needs to be controlled. If D90 is too large, it means that there are many large particles, causing molding defects and affecting the sintering performance, strength and permeability. The peak intensity ratio of 220 crystal plane / 200 crystal plane is controlled in the range of 1.2-2.5, which can ensure that the molding is not easy to disintegrate and the sintered body has excellent strength. The average crystallite diameter of the grains is The pore defects of the grains can be ensured to be small, which effectively avoids affecting the strength and permeability of the sintered body and realizes low-temperature sintering. In the present invention, the specific surface area, particle size, peak intensity ratio of 220 crystal plane / 200 crystal plane and average crystallite diameter of the zirconia ceramic powder are controlled. The zirconia ceramic powder that meets the above numerical range has a specific crystal plane orientation, so low-temperature sintering can be realized without adding sintering aids, and a sintered body with high strength and high sintering density can be obtained.

[0168] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A zirconium oxide ceramic powder, characterized in that: The invention comprises a solid solution formed by zirconium oxide and a stabilizer, wherein the specific surface area of ​​the zirconium oxide ceramic powder is 10 to 32 m 2 / g, an average particle size D50 of 0.1 to 0.3 μm, an average particle size D90 of 0.2 to 0.5 μm, a peak intensity ratio of 220 crystal plane / 200 crystal plane of the zirconia ceramic powder measured by powder X-ray diffraction of 1.2 to 2.5, and an average crystallite diameter of the zirconia ceramic powder obtained by the (-111) plane peak of the zirconia ceramic powder grains in the X-ray diffraction measurement of 2. The zirconium oxide ceramic powder according to claim 1, characterized in that: in, The 2θ angle corresponding to the 220 crystal plane is 49.5° to 50.5°, the 2θ angle corresponding to the 200 crystal plane is 29.5° to 30.5°, and the 2θ angle corresponding to the (-111) crystal plane is 31° to 32°.

3. The zirconium oxide ceramic powder according to claim 1, characterized in that: The sintering starting point of the zirconia ceramic powder is lower than 1300° C., and the sintering starting point is obtained based on DIL test measurement.

4. The zirconium oxide ceramic powder according to claim 1, characterized in that: The stabilizer includes at least one of a Y source, a Ca source, a Mg source and an Er source; Preferably, the Y source includes one or more of yttrium oxide, yttrium nitrate, yttrium chloride and yttrium sulfate; preferably, the content of the Y source relative to the zirconia ceramic powder is 1.5-5 mol%; Preferably, the Ca source includes one or more of calcium oxide, calcium carbonate and calcium chloride; preferably, the content of the Ca source relative to the zirconium oxide ceramic powder is 4 to 8 mol%; Preferably, the Mg source includes one or more of magnesium oxide, magnesium chloride and magnesium sulfate; preferably, the content of the Mg source relative to the zirconia ceramic powder is 6 to 13 mol%; Preferably, the Er source is erbium oxide; preferably, the content of the Er source relative to the entire zirconium oxide powder is 3-5 mol%.

5. The zirconium oxide ceramic powder according to claim 1, characterized in that: The zirconia ceramic powder further includes at least one of 0.005-1wt% of a first dopant that produces a coloring effect and 0.005-1wt% of a second dopant that improves toughness and low-temperature aging properties; Preferably, the first dopant includes at least one of Fe, Er, Mn, Co, Cr, Tb, Pr, Nd, Eu and Ti; Preferably, the second dopant is Al; Preferably, the Al includes one or more of aluminum oxide, aluminum chloride and aluminum nitrate.

6. A method for preparing the zirconium oxide ceramic powder according to any one of claims 1 to 5, characterized in that: It includes: S1. Prepare a soluble zirconium salt into a solution with a zirconium ion concentration of 0.3-0.7 mol / L, perform a hydrothermal reaction at a pressure of 0.2-0.35 MPa and a temperature of 120-140° C. for 12-50 hours, add a stabilizer to the product, and obtain a reaction solution; S2, drying the reaction solution and calcining it, the calcination temperature is 950-1150° C., the heating rate is 2.5-6° C. / min, and the insulation time is 1-5h to obtain a calcined powder; S3. Ball-milling the calcined powder to obtain zirconium oxide ceramic powder, with the ball-milling time being 0.5-6 h.

7. The method for preparing zirconium oxide ceramic powder according to claim 6, characterized in that: The zirconium salt includes at least one of zirconium oxychloride, zirconium acetate and zirconium carbonate.

8. A zirconia sintered body, characterized in that: The method comprises sintering the zirconia ceramic powder prepared by the zirconia ceramic powder as claimed in claims 1 to 5 or the method for preparing the zirconia ceramic powder as claimed in any one of claims 6 to 7 under normal pressure.

9. The zirconia sintered body according to claim 8, characterized in that The pressureless sintering includes sequentially performing dry pressing, isostatic pressing, pre-sintering and sintering; Preferably, the dry pressing pressure of the dry pressing molding is 120-300 MPa, and the dry pressing time is 30-180 s; Preferably, the isostatic pressing pressure of the isostatic pressing is 150-350 MPa, and the isostatic pressing time is 5-20 min; Preferably, the pre-sintering temperature is 800-1100° C., and the pre-sintering time is 15h-60h; Preferably, the sintering temperature is 1150° C.-1400° C., and the sintering time is 30 min-10 h.

10. The zirconia sintered body according to claim 9, characterized in that The sintering density of the zirconium oxide sintered body is ≥99%, the strength is 700-1300 MPa, and the permeability is 38-44%.

Citation Information

Patent Citations

  • Black zirconium-oxide sintered body and preparing method and application thereof

    CN106431394A

  • Method for sintering zirconium oxide ceramic at low temperature

    CN108147814A

  • Composite zirconium oxide powder method as well as preparation method and application thereof

    CN110372397A

  • Nano zirconium oxide material as well as preparation method and application thereof

    CN111320479A

  • Nano zirconium oxide powder, preparation method thereof, obtained dispersion liquid and optical film

    CN112429771A

Cited By

  • Cold-sintered zirconia ceramic and preparation method thereof

    CN120040181A

  • Zirconia ceramic powder and preparation method therefor, and zirconia sintered body

    WO2026129520A1